2016
DOI: 10.1186/s12909-016-0596-2
|View full text |Cite
|
Sign up to set email alerts
|

Residents in difficulty: a mixed methods study on the prevalence, characteristics, and sociocultural challenges from the perspective of residency program directors

Abstract: BackgroundThe majority of studies on prevalence and characteristics of residents in difficulty have been conducted in English-speaking countries and the existing literature may not reflect the prevalence and characteristics of residents in difficulty in other parts of the world such as the Scandinavian countries, where healthcare systems are slightly different. The aim of this study was to examine prevalence and characteristics of residents in difficulty in one out of three postgraduate medical training region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The remediation rate of 4.3% in our cohort is consistent with literature reported values of 2% to 9%. [1][2][3][4][5][6] Further, the demographics of the residents in this study (Table 1) are comparable to other family medicine residency programs in Canada (see annual reports from the Canadian Post-MD Education Registry, www.caper.ca/ en/post-graduate-medical-education/ annual-census). Finally, family medicine residency training in Canada is accredited by the College of Family Physicians of Canada, and is relatively consistent across Canada in terms of the clinical rotations and experiences that are offered.…”
Section: Discussionmentioning
confidence: 82%
“…The remediation rate of 4.3% in our cohort is consistent with literature reported values of 2% to 9%. [1][2][3][4][5][6] Further, the demographics of the residents in this study (Table 1) are comparable to other family medicine residency programs in Canada (see annual reports from the Canadian Post-MD Education Registry, www.caper.ca/ en/post-graduate-medical-education/ annual-census). Finally, family medicine residency training in Canada is accredited by the College of Family Physicians of Canada, and is relatively consistent across Canada in terms of the clinical rotations and experiences that are offered.…”
Section: Discussionmentioning
confidence: 82%
“…17 For some residents, never being given the opportunity to make decisions may lead to difficulty. This is a particular struggle in neurology, where, for many diseases, an aging population is confronted with a lack of disease-modifying treatment options, and where a typical patient evaluation and examination can take an hour or more.…”
Section: The Challenge Of a Changing Technological Landscapementioning
confidence: 99%
“…Christensen et al interviewed residency directors and found that sociocultural problems like inadequate feedback and perceived priority of efficient patient care before education may explain why some residents have difficulty. 17 For some residents, never being given the opportunity to make decisions may lead to difficulty. Despite all of the increasing demands on the health care system, public expectations for professionalism and quality are at an all-time high.…”
Section: The Challenge Of a Changing Technological Landscapementioning
confidence: 99%
“…The warning signs of a doctor in difficulty [27][28][29][30]. Exhibits frequent mood swings, such as irritability or being easily moved to anger or tears in challenging situations.Lacking in insightRejection, becoming defensive, or responding poorly to constructive feedback on performance, lack of ability to reflect on situations.…”
mentioning
confidence: 99%